Equity, options, and bank strategies - Razul, A.; Gomes, O.; Gulamhussen, M. A. (Annals of Economics and Finance, 2025)
We build on existing literature to develop a stylized model of a bank in which managers can receive variable pay through stocks or options. The model shows both modalities aligning managers' and shareholders' interests. However, options allow determining a performance contingent optimal. This options' feature is desirable in mitigating perverse implications for depositors emerging from the alignment of managers' and shareholders' interests through equity. Exercises against the model's simulated and real data corroborate the model's findings. Our findings can be useful for banks in setting variable pay modes and regulators and supervisors in addressing the implications of different pay modes.